Magnetic Characterization of Sediment Source‐To‐Sink Processes in the Bengal Fan Since 45 ka - Rong Huang; Liao Chang; Shishun Wang; Pengfei Xue; Shengfa Liu; Xuefa Shi; Somkiat Khokiattiwong; Narumol Kornkanitnan (Geochemistry, Geophysics, Geosystems)
Abstract The Bengal Fan is the largest submarine fan on Earth with a complex submarine channel system. Therefore, it is challenging to understand the evolution of Bengal Fan sediment source‐to‐sink processes. Here we present a synthesis of high‐resolution environmental magnetic records of five sediment cores from the central and lower Bengal Fan to reconstruct sedimentation history for the past 45 ka. Rock magnetic measurements and electron microscopic analyses reveal that detrital (titano)magnetites are the dominant magnetic minerals in the central fan sediments, while lower fan deposits exhibit enhanced magnetofossil contribution. During the last three marine isotope stages, glacial periods have increased detrital magnetic mineral concentration and grain size compared with interglacial periods. This increase is primarily attributed to the weakening of the Indian summer monsoon. Spatially, magnetic mineral concentration and grain size show decreasing trends from north to south and from east to west in the Bengal Fan, which may be modulated by submarine channel shifts. Deposition center migration driven by sea level fluctuations and sediment provenance variations were key factors controlling magnetic mineral concentration and grain size. Therefore, magnetic proxies serve as sensitive indicators of sedimentation patterns within the Bengal Fan. The spatiotemporal distribution of magnetic particles provides valuable insights into the source‐to‐sink dynamics and the dominant factors affecting sediment transportation in global submarine fans.